Electrical stability during redox cycles promoted by Pd exsolution in LSFPd thin films. Issue 9 (1st May 2022) - Liu, Zhao; Duranti, Leonardo; Di Bartolomeo, Elisabetta; Yang, Nan
Abstract: Exsolution of metallic nanoparticles ( NPs ) from oxide supports offers a novel approach to design high-performance materials in the field of heterogeneous catalysis and energy conversion and storage. Here, we report the homogenous exsolution of Pd NP s with an average size of 100 nm in compressive strained La0.6 Sr0.4 Fe0.9 Pd0.1 O3-δ (LSFPd) thin films. We systematically explored the electrical resistivity and the redox stability of LSFPd thin films upon exsolution of NP s. Compared to La0.6 Sr0.4 FeO3-δ (LSF) thin films, whose electrical response was controlled by oxygen stoichiometry, LSFPd films showed a more stable electrical response in redox cycling with similar resistivity values both in air and hydrogen. The improved stability was attributed to dynamic and exsolution of NP s. Our study showed that the control of exsolution of NP s can provide a new way to regulate the electrical response of perovskite oxide semiconductors under external stimuli (i.e., atmosphere), which could be beneficial for the rational design of high-performance functional materials for micro solid oxide fuel cells, nano-sensors, and nano-actuators applications. Graphical abstract: In addition to increased oxygen vacancies emerging from LSF crystal lattice after the reduction treatment, Pd ions doped in the B-site of perovskite could be reduced and exsolved as NPs on the surface of LSFPd films, leading to the improved stability of electrical response. Image 1